2016
DOI: 10.1016/j.jns.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Essential tremor-Parkinson's disease: A double whammy

Abstract: Background Surprisingly little has been written about the combined clinical entity, essential tremor-Parkinson’s disease (ET-PD), which is the result of a double disease hit. We carefully quantified tremor burden using a wide range of measures (tremor severity, tremor-related disability, tremor-related quality of life) and furthermore, studied additional motor and non-motor features in ET-PD. Methods In this prospective, clinical-epidemiological study, we performed a standardized, structured clinical evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
17
0
3
Order By: Relevance
“…In addition, the presence of bradykinesia in patients with HD may indicate a specific disease variant, namely, the Westphal variant. Patients with hyperkinetic movement disorders may also develop bradykinesia during the disease course, as in late stage HD [84] or in ET‐PD [186]. This also implies that patients who have initially been diagnosed with a non‐parkinsonian condition may possibly require treatment for bradykinesia when clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of bradykinesia in patients with HD may indicate a specific disease variant, namely, the Westphal variant. Patients with hyperkinetic movement disorders may also develop bradykinesia during the disease course, as in late stage HD [84] or in ET‐PD [186]. This also implies that patients who have initially been diagnosed with a non‐parkinsonian condition may possibly require treatment for bradykinesia when clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Some elderly individuals may therefore have both ET and PD by chance alone. There is ongoing debate over the frequency of co‐occurrence, clinical diagnosis, course, long‐term clinical profile, different PS variants, and the significance of the co‐prevalence of PS in ET cases …”
mentioning
confidence: 99%
“…Several clinical and epidemiological studies have reported on the ET‐PD co‐prevalence . Significance of such studies is limited because the brain pathology was not identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…При сравнительном анализе моторных симптомов не выявлено различий между группами ЭТ-БП и БП на одинаковых стадиях болезни [20,24,25]. Ряд авторов сходится во мнении, что выраженность тремора у пациентов с ЭТ-БП больше, чем у пациентов с БП и даже ЭТ [20,[25][26][27][28], и только в исследовании R.М. Simoes и соавт.…”
unclassified